2008
DOI: 10.1111/j.1525-142x.2008.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

RNAi analysis of nubbin embryonic functions in a hemimetabolous insect, Oncopeltus fasciatus

Abstract: Although the expression of the POU homeodomain gene nubbin (nub) has been examined in several arthropod species, its function has been studied only in Drosophila. Here, we provide the first insight into functional roles of this gene in a hemimetabolous insect species, Oncopeltus fasciatus. The analysis of its function using RNAi resulted in the altered morphology of antennae and labial tubes in the head, legs in the thorax, and, most notably, the growth of ectopic appendages originating from abdominal segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 60 publications
1
35
3
Order By: Relevance
“…Data from other genes and taxa also suggest mixed support for the two hypotheses. For example, pdm / nubbbin has exceptionally labile expression (Li and Popadić 2004) and functional domains (Hrycaj et al 2008; Turchyn et al 2011) among insects, but there is some consistency across special homologs, as predicted by the independent model. More extensive comparative functional studies will be necessary in the future to evaluate the extent of developmental dependence among serial homologs, and to examine whether genes involved in certain developmental processes are more prone to divergence in limited or universal ways.…”
Section: Discussionmentioning
confidence: 99%
“…Data from other genes and taxa also suggest mixed support for the two hypotheses. For example, pdm / nubbbin has exceptionally labile expression (Li and Popadić 2004) and functional domains (Hrycaj et al 2008; Turchyn et al 2011) among insects, but there is some consistency across special homologs, as predicted by the independent model. More extensive comparative functional studies will be necessary in the future to evaluate the extent of developmental dependence among serial homologs, and to examine whether genes involved in certain developmental processes are more prone to divergence in limited or universal ways.…”
Section: Discussionmentioning
confidence: 99%
“…The gap gene candidates that were examined included Bm-ems (Bombyx empty spiracles) and Bm-kr. Bm-nub (Bombyx nubbin) was also examined because the orthologs of these genes appeared to show gap-like expression in the abdomen (Hrycaj et al, 2008). Of these, Bm-ems and Bm-nub was identified in this study (see Materials and methods).…”
Section: Gene Regulatory Interactions During Early Bombyx Embryogenesismentioning
confidence: 99%
“…However, what is only now becoming evident is that there may be an extensive amount of lineage-specific variation in these networks. For example, a recent functional analysis of the paired-domain gene nubbin ( nub ) in the milkweed bug Oncopeltus fasciatus has shown that the limbless abdomen is established differently as compared to Drosophila (Hrycaj et al, 2008). In a similar fashion, functional studies of the homeotic gene Cephalothorax ( Cx ), an ortholog of Sex combs reduced ( Scr ), have shown that in the absence of this gene, an extra supernumerary segment forms between the labial and T1 segments in Tribolium (Shippy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%